Thinking Out of the Box: Galician and the Other Languages - Basalo Bembibre, Pedro (Madrygal. Revista de Estudios Gallegos, 2024)
The purpose of this article is to refute the Castilian-centric view, assumed by many Galician speakers, in which Spanish is the only valid and socially accepted reference, either as a norm and model of a standard language or as a channel of communication with other people outside of Galicia. In order to dismantle this prejudice, the connection between Galician and other European languages is illustrated by means of lexical, grammatical and phonological-phonetic aspects, as well as its usefulness when learning other languages